White coat, patient gown. Issue 2 (31st March 2014) - Wellbery, Caroline; Chan, Melissa
Abstract : Much has been written about the symbolic function of the white coat: its implications of purity, its representation of authority and professionalism, and its role in consolidating a medical hierarchy. By contrast, the medical literature has paid almost no attention to the patient gown. In this article, we argue that in order to understand the full implications of the white coat in the doctor–patient relationship, we must also take into account patients' dress, and even undress. We explore contemporary artistic images of white coat and patient gown in order to reveal the power differential in the doctor–patient relationship. Artistic representations capture some of the cultural ambivalence surrounding the use of the white coat, which confers professional status on its wearer, while undermining his or her personal identity. At the other end of the sartorial spectrum, hospital gowns also strip wearers of their identity, but add to this an experience of vulnerability. Although compelling reasons for continuing to wear the white coat in circumscribed settings persist, physicians should be mindful of its hierarchical implications. Ample room remains for improving patients' privacy and dignity by updating the hospital gown.